Dopant Concentration and Effective Atomic Number of Copper-Doped Potassium Borate Glasses - I. Hossain; N. K. Shekaili; H. Wagiran (Advances in Materials Science and Engineering)
Copper-doped (0.5 mol%) and undoped potassium borate glasses have been prepared by the composition of (100-x)H3BO3 + xK2CO3, where 10 ≤ x ≤ 30 mol % by the traditional melting quenching method. The structural pattern of glasses with different composition has been identified by X-ray diffraction (XRD). The glow curves were analysed to determine various characterizations of the TLDs. Identification of the compositions and concentrations and effective atomic number of undoped and doped potassium borate glass was carried out using scanning electron microscope analysis (SEM). The dopant concentrations are found to be 0.25 mol%, while Zeff are 11.42 and 10.48 for Cu-doped and undoped potassium borate glasses, respectively.